IDENTIFICATION OF pH SENSOR SENSITIVITY LEVELS ACROSS VARIOUS AQUATIC ECOSYSTEMS BASED ON DIRECT MEASUREMENT WITH WIRELESS DATA COMMUNICATION - Halil Akhyar; Ariyan Zubaidi; Ramaditia Dwiyansaputra; Mohammad Zaenuddin Hamidi; Susi Rahayu; Kasnawi Al Hadi; Ni Ketut Anggriani (Universitas Mataram, 2026)
Characterizing sensor sensitivity across various aquatic ecosystems is essential for determining the sensor's ability to accurately detect pH changes under real-world field conditions. Given this context, this study aims to assess the sensitivity of a capacitive pH sensor in several aquatic ecosystems through in situ measurements. This study utilized several water samples for direct calibration and testing. Four water samples with known pH levels were used for calibration. For the subsequent testing phase, water samples were collected from the following ecosystems: ecosystem 1 (river), ecosystem 2 (rice field), ecosystem 3 (estuary), ecosystem 4 (sea), and ecosystem 5 (fish pond). The system was built using an Arduino MEGA+ESP8266 microcontroller. Regarding the sensor component, a pH sensor (DF-Robot) with an analog signal output was employed. The calibrated system was examined using five different water ecosystems. The results show that the system was calibrated, with a span of 6.47-7.50. The sensitivity levels depend on the ecosystem conditions (0.08 V/pH level). The findings are expected to provide a scientific basis for developing more reliable pH sensors and to support sustainable water quality monitoring and mitigation efforts.